Environmental Chemicals in Breast Milk and Formula: Exposure and Risk Assessment Implications - Lehmann, Geniece M.; LaKind, Judy S.; Davis, Matthew H.; Hines, Erin P.; Marchitti, Satori A.; Alcala, Cecilia; Lorber, Matthew (Environmental health perspectives, 2018)
Human health risk assessment methods have advanced in recent years to more accurately estimate risks associated with exposure during childhood. However, predicting risks related to infant exposures to environmental chemicals in breast milk and formula remains challenging. Our goal was to compile available information on infant exposures to environmental chemicals in breast milk and formula, describe methods to characterize infant exposure and potential for health risk in the context of a risk assessment, and identify research needed to improve risk analyses based on this type of exposure and health risk information. We reviewed recent literature on levels of environmental chemicals in breast milk and formula, with a focus on data from the United States. We then selected three example publications that quantified infant exposure using breast milk or formula chemical concentrations and estimated breast milk or formula intake. The potential for health risk from these dietary exposures was then characterized by comparison with available health risk benchmarks. We identified areas of this approach in need of improvement to better characterize the potential for infant health risk from this critical exposure pathway. Measurements of chemicals in breast milk and formula are integral to the evaluation of risk from early life dietary exposures to environmental chemicals. Risk assessments may also be informed by research investigating the impact of chemical exposure on developmental processes known to be active, and subject to disruption, during infancy, and by analysis of exposure-response data specific to the infant life stage. Critical data gaps exist in all of these areas. Better-designed studies are needed to characterize infant exposures to environmental chemicals in breast milk and infant formula as well as to improve risk assessments of chemicals found in both foods. https://doi.org/10.1289/EHP1953.